Laparoscopic ileo-transverse bypass may contribute to achieving curative resection for locally advanced right colon cancer: a case report - Shunsuke Tabe; Toru Tonooka; Isamu Hoshino; Nobuhiro Takiguchi; Hiroaki Soda; Hisashi Gunji; Yoshihiro Nabeya; Masayuki Ohtsuka (Surgical Case Reports, 2021)
Abstract Background The strategy for treating obstructive colon cancers with metastatic lesions remains unclear. Herein, we report a case of laparoscopic ileo-transverse colon bypass (LITB) before preoperative chemotherapy for an obstructive right colon cancer. Case presentation A 59-year-old woman was referred to our institution (Department of Gastroenterological Surgery, Chiba Cancer Center) for liver tumors detected on ultrasound. The clinical diagnosis was ascending colon cancer with multiple liver metastases. Based on the criteria of the International Union against Cancer Committee, 8th edition, the staging was confirmed as cT4aN1M1a(H), cStage IV. Although the primary tumor in the ascending colon extended beyond the colonic wall, curative resection was possible for both primary and metastatic tumors. We planned to administer chemotherapy before the radical surgery to obtain tumor-free resection margins; however, as the obstruction was fatal, LITB was prioritized and performed using five ports. An intracorporeal side-to-side anastomosis was performed between the ileum, 25 cm from the terminal ileum, and the transverse colon. The patient was discharged on postoperative day 18 without any complications. After LITB, for preoperative chemotherapy, five courses of capecitabine plus oxaliplatin (CapeOX) + bevacizumab were administered. Six weeks after the preoperative chemotherapy, right hemicolectomy with D3 lymph node dissection and right hepatectomy were performed. Pathological findings of the resected specimen confirmed curative resection of both lesions, and a favorable effect of chemotherapy was obtained. The patient has been alive for over 8 months after the surgery, with no evidence of cancer recurrence. Conclusions This case report demonstrates the effectiveness of LITB for obstructive right colon cancer in patients who need preoperative chemotherapy.